Synthesis of [13C4]‐labeled 2′‐deoxymugineic acid. (10th November 2014) - Walter, Martin R.; Artner, Daniel; Stanetty, Christian
<x xml:space="preserve">Abstract</x> The phytosiderophore 2′‐deoxymugineic acid (DMA) is exuded via the root system by all grasses (including important crop plants like rice, wheat and barley) to mobilize Fe(III) from soil and improve plant Fe nutrition, crucial for high crop yields. Elucidation of the biogeochemistry of 2′‐deoxymugineic acid in the rhizosphere requires its quantification in minute amounts. To this end, 13C4‐DMA was synthesized for the first time, from cheap isotopically labeled starting materials. The synthetic route utilizes l‐allyl(13C2)glycine and l‐(2‐13C)azetidine (13C)carboxylic acid as versatile labeled building blocks. The title compound was recently used as an internal standard for analysis of soil and plant samples allowing the first accurate quantification of DMA in these matrices by means of LC‐MS/MS. It is furthermore used in tracer experiments investigating biodegradation of DMA in soil.